2012
DOI: 10.1590/s1415-43662012001000009
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e produtividade do pinhão-manso em função do espaçamento e irrigação

Abstract: Objetivou-se, com este trabalho, avaliar o efeito do espaçamento e da complementação hídrica no crescimento e produtividade do pinhão-manso. O experimento foi conduzido na área experimental do Instituto Federal Goiano, campus Rio Verde,GO, no período de 12/09/2009 a 30/04/2011, no delineamento de blocos casualizados com três repetições, os fatores foram sete espaçamentos e duas condições hídricas, cada parcela constituída de 16 plantas, sendo as quatro plantas centrais a área útil. Aos 60 dias após o transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
5
0
5
Order By: Relevance
“…Drumond et al (2010) and Horschutz, Teixeira, Alves, Silva and Silva (2012) found a positive relation between the use of irrigation and the growth and development of Jatropha plants in the region of Petrolina, Pernambuco State.…”
Section: Resultsmentioning
confidence: 96%
“…Drumond et al (2010) and Horschutz, Teixeira, Alves, Silva and Silva (2012) found a positive relation between the use of irrigation and the growth and development of Jatropha plants in the region of Petrolina, Pernambuco State.…”
Section: Resultsmentioning
confidence: 96%
“…All the analysis, as well as the generation of charts and maps were made with software R 3.1.0 (R Development Core Team, 2014), using the geoR Horschutz et al (2012), who found CV values of 11.36% in irrigated Jatropha plantations and in rain fed conditions in the state of Goiás, at 480 days after transplanting.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies are being conducted in order to evaluate the productive capacity of jatropha in Brazil (HORSCHUTZ et al, 2012;SIQUEIRA et al, 2012;VERAS et al, 2011;NERY et al, 2009;NERY et al, 2013). Despite the species great production potential in the country semiarid region (DRUMOND et al, 2010), the lack of research results on its cultivation is still great, especially in relation to the spatial dependence of its growth characteristics, such as stem diameter and plant height.…”
Section: Introductionmentioning
confidence: 99%
“…No sistema SASP, o espaçamento 6x3 m apresentou os maiores valores para a variável, tendo diferido dos demais tratamentos nas duas safras (50,47 e 86,97, respectivamente). Horschutz et al (2012) constataram efeito de espaçamento de plantio em plantas de pinhão-manso aos 480 dias após o plantio e que espaçamentos menos adensados apresentaram maiores áreas foliares por planta. Isso representa maior capacidade das plantas em aproveitar a energia solar, o que pode explicar o maior crescimento de plantas estabelecidas em espaçamentos mais amplos (González-Sanpedro et al, 2008).…”
Section: Resultsunclassified